Injury outcome indicators: the development of a validation tool. Issue 1 (3rd February 2005) - Cryer, C; Langley, J D; Jarvis, S N; Mackenzie, S G; Stephenson, S C R; Heywood, P
Abstract : Background: Researchers have previously expressed concern about some national indicators of injury incidence and have argued that indicators should be validated before their introduction. Aims: To develop a tool to assess the validity of indicators of injury incidence and to carry out initial testing of the tool to explore consistency on application. Methods: Previously proposed criteria were shared for comment with members of the International Collaborative Effort on Injury Statistics (ICE) Injury Indicators Group over a period of six months. Immediately after, at a meeting of Injury ICE in Washington, DC in April 2001, revised criteria were agreed over two days of meetings. The criteria were applied, by three raters, to six non-fatal indicators that underpin the national road safety targets for Canada, New Zealand, and the United Kingdom. Consistency of ratings were judged. Consensus outcome: The development process resulted in a validation tool that comprised criteria relating to: (1) case definition, (2) a focus on serious injury, (3) unbiased case ascertainment, (4) source data for the indicator being representative of the target population, (5) availability of data to generate the indicator, and (6) the existence of a full written specification for the indicator. On application of these criteria to the six road safety indicators, some problems of agreement between raters were identified. Conclusion: This paper has presented an early step in the development of a tool for validating injury indicators, as well as some directions that can be taken in its further development.